Obstetric and neonatal complications among women with autoimmune disease. (September 2019) - Williams, Andrew; Grantz, Katherine; Seeni, Indulaxmi; Robledo, Candace; Li, Shanshan; Ouidir, Marion; Nobles, Carrie; Mendola, Pauline
Abstract: Background: The impact of autoimmune diseases on pregnancy remains understudied on a population level. Examination of obstetric and neonatal outcomes among women with autoimmune disease and their infants can provide important insights for clinical management. Methods: Autoimmune diseases and outcomes were identified using medical records. Cesarean delivery, preterm birth, preeclampsia, small for gestational age (SGA), neonatal intensive care (NICU) admission, neonatal respiratory distress syndrome (RDS), and perinatal mortality risk was assessed. Poisson regression with robust standard errors estimated relative risks (RR) and 95% confidence intervals (95% CI) with adjustment for maternal characteristics and other chronic conditions. Results: Women with T1DM were at increased risk for nearly all outcomes including RDS (RR: 3.62; 95% CI: 2.84, 4.62), perinatal mortality (RR: 2.35; 95% CI: 1.12, 4.91), cesarean delivery (RR: 2.16; 95% CI: 2.02, 2.32) and preterm birth (RR: 3.52; 95% CI: 3.17, 3.91). Women with SLE also had higher risk for preterm delivery (RR: 2.90; 95% CI: 2.42, 3.48) and RDS (RR:2.99; 95% CI: 1.99, 4.51) as did women with Crohn's (cesarean delivery RR:1.31, 95% CI: 1.08, 1.60; preterm delivery RR: 1.84, 95% CI: 1.37, 2.49. RA increased risk for SGA (RR:1.66; 95% CI: 1.08, 2.55). Conclusion(s): Despite the heterogeneity in autoimmune diseases, we observed elevated preterm birth risk for most women with autoimmune disease. SLE and T1DM appeared to confer increased risk for a wide range of adverse outcomes. Highlights: Across a spectrum of autoimmune disease, risk for adverse obstetric and neonatal outcomes is high. Preterm birth and cesarean delivery risks were notably higher for women with autoimmune disease. Clinical indications for cesarean delivery were similar across types of autoimmune diseases. Type 1 diabetes mellitus conferred the highest risk for most poor obstetric and neonatal outcomes.